The hospitality consumption experiences of parents and carers with children: A qualitative study of foodservice settings. (April 2016) - Lugosi, Peter; Robinson, Richard N.S.; Golubovskaya, Maria; Foley, Laura
Highlights: Identifies factors that frustrate, satisfy and delight parents/carers with children. Performing childcare frames carers' needs and perceptions of (dis)satisfiers. Experiences of (in)hospitality shaped by design, services and staff/patron practices. Children's agency and wellbeing are key to influencing the overall experience. Recognising and responding to the 'work' of childcare can improve experiences. Abstract: Drawing on research conducted in Australia and the United Kingdom, this paper addresses two questions: first, how is parenting and childcare provision performed within restaurants, cafes and pubs; and second, how are different aspects of hospitality provision entangled with parent, carer and children's experiences? The findings show how gestures of hospitality, particularly service interactions that are tailored to meet the specialist needs of these consumers, can create positive emotions and encourage customer loyalty. Furthermore, the data show the importance of recognising children as sovereign consumers. We conclude that responding directly to children's needs can augment their experiences and hence, those of their carers and other patrons. The paper identifies a number of implications for management practice and several avenues for future research.